Pemeranan Tokoh Agus Tubagus dalam Naskah Pinangan Karya Anton P. Chekov Saduran Suyatna Anirun Menggunakan Metode Akting Stanislavsky - Wardana, Aditiya; Alamo, Enrico; Sulaiman, Sulaiman (Jurnal Cerano Seni : Pengkajian dan Penciptaan Seni Pertunjukan, 2026)
The role of the character Agus Tubagus in the Pinangan script by Anton P. Chekov adapted by Suyatna Anirun is a form of creative effort carried out by the actor to realize the character of Agus Tubagus which is based on the interpretation of the character performed on stage, the embodiment of the character Agus Tubagus uses the Stanislavsky acting method Magic If approach. The process of realizing the character of Agus Tubagus uses methods including; observation, identifying the character, developing the character, animating the character, controlling emotions and dressing the character. The Pinangan script by Anton P. Chekov adapted by Suyatna Anirun contains a story of social reality about a 30-year-old man, Agus Tubagus, who wants to propose to a girl named Ratna Rukmana.